ORGANIC AND MINERAL FERTILIZATION STRATEGIES FOR IMPROVED SOYBEAN PRODUCTION - Carlos , Eduardo Silva; Mariana , Gabriela Oliveira; Felipe , Henrique Costa (Advanced Journal of Environmental Sciences (AJES), 2024)
Soybean (Glycine max L.) farming is of paramount global and socioeconomic significance, especially in Brazil, where it is cultivated across all states. As the primary agricultural commodity in the country, its economic impact is substantial, driven by its diverse range of products derived from its grains (MAPA, 2016). The 5th monitoring report of the Brazilian grain harvest for the 2022/2023 period, published by CONAB (2023), highlights Goiás’ prominent role in national soybean production. In the 2021/2022 harvest, Goiás ranked third in the country with a production of 28,834.4 thousand tons, following Mato Grosso and Paraná. This data underscores the critical contribution of Goiás to Brazil’s soybean industry and its significant position within the global agricultural market